2020
DOI: 10.1074/jbc.rev120.011202
|View full text |Cite
|
Sign up to set email alerts
|

Structure, mechanism, and regulation of mitochondrial DNA transcription initiation

Abstract: Mitochondria are specialized compartments that produce requisite ATP to fuel cellular functions and serve as centers of metabolite processing, cellular signaling, and apoptosis. To accomplish these roles, mitochondria rely on the genetic information in their small genome (mitochondrial DNA) and the nucleus. A growing appreciation for mitochondria's role in a myriad of human diseases, including inherited genetic disorders, degenerative diseases, inflammation, and cancer, has fueled the study of biochemical mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 226 publications
(349 reference statements)
0
49
0
Order By: Relevance
“…Mitochondrial DNA (mtDNA) is packaged with specific proteins in compact DNA–protein complexes named mitochondrial nucleoids (mt-nucleoids). Abf2 is a mtDNA-binding protein, which plays a prominent role in the packaging of mtDNA into the nucleoid structure ( Basu et al, 2020 ) that protects mtDNA against damage ( Miyakawa, 2017 ). The analysis of an abf2Δ mutant showed that when grown on media containing a fermentable carbon source, cells lose mtDNA and become respiratory deficient (petite) ( Miyakawa, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) is packaged with specific proteins in compact DNA–protein complexes named mitochondrial nucleoids (mt-nucleoids). Abf2 is a mtDNA-binding protein, which plays a prominent role in the packaging of mtDNA into the nucleoid structure ( Basu et al, 2020 ) that protects mtDNA against damage ( Miyakawa, 2017 ). The analysis of an abf2Δ mutant showed that when grown on media containing a fermentable carbon source, cells lose mtDNA and become respiratory deficient (petite) ( Miyakawa, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 38th protein-humanin (encoded by 16S rRNA)-has protective activities against apoptosis-mediated diseases [37]. All other proteins required for the mitochondria regulation, maintenance and repair are encoded by the nuclear genome [38].…”
Section: Role Of Mitochondria In Pcosmentioning
confidence: 99%
“…Mitochondria are the only organelles in human cells that have their own genetic material except for the nucleus. Compared with nuclear genes, the mitochondrial genome has its specific features (5). mtDNAs exist in mitochondria and cells in multiple copies.…”
Section: Mitochondrial Geneticsmentioning
confidence: 99%
“…Except for the respiratory chain complex protein which is double-encoded by mitochondrion genome (mtDNA) and nuclear genes, all other proteins are encoded by nuclear genes. Therefore, mtDNA mutations or nuclear gene mutations may cause mitochondrial dysfunction (4,5).…”
mentioning
confidence: 99%